1992
DOI: 10.1007/bf02598002
|View full text |Cite
|
Sign up to set email alerts
|

Detection of pyuria and bacteriuria in symptomatic ambulatory women

Abstract: The standard urinalysis was the most accurate single method to predict significant bacteriuria in symptomatic ambulatory women. Sequencing the dipstick urinalysis with the standard urinalysis may be a cost-effective approach to evaluating these patients in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 22 publications
3
22
0
Order By: Relevance
“…This implies that to use significant pyuria to diagnose or predict bacteriuria in children with SCA will result in significantly large numbers of false-positive and falsenegative results. The high sensitivity obtained in this study is comparable to that of Smith et al 10 as well as Blum et al 13 who reported sensitivities of significant pyuria to be 64% and 98% among subjects with significant bacteriuria. The specificity in our study was low in contrast with specificity of 68% reported by Blum et al 13 The use of symptomatic women as their sample population for the study may contribute to the observed significant difference.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This implies that to use significant pyuria to diagnose or predict bacteriuria in children with SCA will result in significantly large numbers of false-positive and falsenegative results. The high sensitivity obtained in this study is comparable to that of Smith et al 10 as well as Blum et al 13 who reported sensitivities of significant pyuria to be 64% and 98% among subjects with significant bacteriuria. The specificity in our study was low in contrast with specificity of 68% reported by Blum et al 13 The use of symptomatic women as their sample population for the study may contribute to the observed significant difference.…”
Section: Discussionsupporting
confidence: 89%
“…However, the absence of pyuria in children with UTI is rare but can occur when a child is been evaluated so early in the course of the infection when the inflammatory response has not yet developed. 13 Many workers, on the contrary, reported low sensitivity of pyuria among children with UTI. 7,14 The higher sensitivity reported in this study as compared to the 55.4% reported by Mava et al 7 may be due to the fact that most of the SCA children with bacteriuria in this study were in SCA crises which could have been precipitated by UTI.…”
Section: Discussionmentioning
confidence: 99%
“…The number of cells attached to the polymer surfaces was determined by hemocytometric counting. 16,17 The mean value of four replicates was used as the final result for each sample. Cell attachment was expressed as a proportion of the number of cells attached to TCPS in the same culture media.…”
Section: Cell Behaviormentioning
confidence: 99%
“…VanNostrand and colleagues 17 found that 78.9% of samples containing nitrate-reducing bacteria were actually negative for nitrite on the urine dipstick. Therefore the presence of nitrite has a high positive predictive value of 94% 18 , but in the absence of urinary nitrite a UTI cannot be ruled out.…”
Section: Urinalysis Part 1: Urine Dipstickmentioning
confidence: 99%
“…If both tests are positive, the specificity increases to 98-99.5%, indicating a high likelihood of a UTI 14,19 . Several studies conclude that from this information alone a diagnosis of a UTI can be made and treatment initiated 2,18,20,21 . This clinical conclusion has recently been called into question by a study demonstrating a low sensitivity for both leukocyte esterase and nitrite but did not take into account the clinical presentation of the patients in the study 17 .…”
Section: Urinalysis Part 1: Urine Dipstickmentioning
confidence: 99%